1989
DOI: 10.1002/jsfa.2740490406
|View full text |Cite
|
Sign up to set email alerts
|

Fungi isolated from packaging materials: Their role in the production of 2, 4, 6‐trichloroanisole

Abstract: Fungi isolated >om fibreboard cartons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 12 publications
1
24
0
3
Order By: Relevance
“…Including the Rio flavor of Brazilian coffee, chlorophenol, bromophenol, chloroanisole and bromoanisole are responsible for claims of off-flavors in drinks and foods, and can cause economic losses. We cannot rule out any possibility that Rio flavor of Brazilian coffee is caused by the decomposition of 2,4,6-TCP and PCP, which has been reported previously, and by disinfection using chlorine (Buser et al, 1982;Chatonnet et al, 2004;Curtis et al, 1974;Fukaya et al, 1994;Goldenberg and Matheson, 1975;Griffith, 1977;Montiel et al, 1999;Ogiwara et al, 2003;Saxby and Wagg, 1985;Tindale et al, 1989;Whitfield et al, 1985;Whitfield et al, 1997).…”
Section: Description By Coffee Tasting Panelists Of Off-flavor Causedmentioning
confidence: 87%
See 1 more Smart Citation
“…Including the Rio flavor of Brazilian coffee, chlorophenol, bromophenol, chloroanisole and bromoanisole are responsible for claims of off-flavors in drinks and foods, and can cause economic losses. We cannot rule out any possibility that Rio flavor of Brazilian coffee is caused by the decomposition of 2,4,6-TCP and PCP, which has been reported previously, and by disinfection using chlorine (Buser et al, 1982;Chatonnet et al, 2004;Curtis et al, 1974;Fukaya et al, 1994;Goldenberg and Matheson, 1975;Griffith, 1977;Montiel et al, 1999;Ogiwara et al, 2003;Saxby and Wagg, 1985;Tindale et al, 1989;Whitfield et al, 1985;Whitfield et al, 1997).…”
Section: Description By Coffee Tasting Panelists Of Off-flavor Causedmentioning
confidence: 87%
“…Both 2,4,6-TCA and 2,6-DCP have a low threshold and cause off-flavors in drinks and foods even at very low concentrations. It should be noted that almost anyone can sense mustiness at high concentrations (Buser et al, 1982;Curtis et al, 1974;Griffith, 1977;Tindale et al, 1989;Whitfield et al, 1985). 2,6-DCP is detected by most persons as a chlorine or disinfection flavor even in minute quantities, and is supposed to be a causal substance of the chlorine odor in Rio flavor.…”
Section: Description By Coffee Tasting Panelists Of Off-flavor Causedmentioning
confidence: 99%
“…Chloroanisoles that cause unpleasant aromas and tastes are not associated solely with wines. In fact, 2,3,4,6-TeCA causes musty taint in chickens (7,13), and other chloroanisoles, including 2,4,6-TCA, also produce off-odor problems in potato chips (6), dried fruit (33,35), coffee (31), and drinking water (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, O methylation of pentachlorophenol (PCP) by Trichoderma virgatum (6), production of 2,3,4,6-TeCA by several fungi (13), and S methylation of several phenolic compounds by the yeast Saccharomycopsis lipolytica (10) and by the protozoans Euglena gracilis (8) and Tetrahymena thermophila (9) have been reported. Also, the ability of some fungal strains isolated from food-packaging materials (33,35) and of several fungi and actinomycetes isolated from drinking water (25) to methylate 2,4,6-trichlorophenol (2,4,6-TCP) to produce 2,4,6-TCA has also been documented.…”
mentioning
confidence: 99%
“…In fact, 2,4,6-TCA has been reported to be responsible for at least 80% of the cases of cork taint (8), and in a recent study Pollnitz and colleagues reported that 2,4,6-TCA could be detected in 100% of tainted wines (23). The role of chloroanisoles as contaminant agents is not restricted to wine, since the presence of these compounds is well documented in other food materials, such as eggs and poultry (12), chickens (11), pulp chips (10), dried fruits (30), Brazilian coffee (29), and drinking water (21).…”
mentioning
confidence: 99%